The relationship of vitamin A, C, and E intake with premature aging of facial skin in female market traders - Chintya Wulandarie; Sumardiyono Sumardiyono; Ratih Puspita Febrinasari (World Nutrition Journal, 2023)
Background: Women's market traders are jobs that are often exposed to free radicals, including air pollution, cigarette smoke, sun exposure and have a high workload that causes stress. Antioxidants can protect the skin from free radicals and can inhibit the process of premature aging of facial skin which are found in vegetables and fruits such as vitamins A, C, E. Objective: To determine the relationship between intake of vitamins A, C, and E with premature aging of market traders in the form of wrinkles around the face. Methods: Observational research with cross sectional method. The sampling technique is multi-stage cluster sampling. This research was conducted at Beringharjo Market with a total sample of 172 respondents with inclusion criteria namely female traders, aged 26–45 years, workers in the market area. The exclusion criteria are tourists/market visitors, women who are pregnant and breastfeeding. The research variables for intake of vitamins A, C, and E used the SQ-FFQ (Semi-Quantitative Food Frequency Questionnaire) questionnaire with the interview method. In measuring the number of wrinkles on facial skin using photoaging through facial shooting using a Sony A7R3 camera with a 24-70 lens that is analyzed by a dermatologist (skin expert). Data analysis technique using multiple logistic regression analysis. This analysis uses SPSS software version 22.0. Results: In the multiple logistic regression test, p = 0.037 (p <0.05) means that there is a relationship between vitamin A intake and premature aging of facial skin. On vitamin C intake, p = 0.436 (p> 0.05), meaning that there is no relationship between vitamin C intake and premature aging of facial skin. And on vitamin E intake, p = 0.171 (p> 0.05) there is no relationship between vitamin E intake and premature aging of facial skin. Conclusion: Intake of vitamin A has a significant relationship with the occurrence of premature aging of the face, but vitamins C and E do not have a significant relationship with the occurrence of premature aging of the facial skin